Management systems and structural quality of a Dusky-Red Latosol (Oxisol) - Naves Silva, Marx Leandro; Curi, Nilton; Blancaneaux, Philippe (Pesquisa Agropecuaria Brasileira, 2000)
This study aimed to evaluate the structural quality of a Dusky-Red Latosol (Oxisol) by the following attributes: aggregate-size distribution, geometrical average diameter of aggregates, aggregates resistance to simulated raindrops impact, and penetration resistance, under no-till and conventional till systems, using the native forest as reference trial. Among the utilized methods, the kinetic energy necessary for destructing the aggregates presented the best distinction among the studied management systems. In the superficial layer, the no-till revealed bigger and more resistant aggregates, being its values of geometrical average diameter and kinetic energy necessary for destructing the aggregates around 1.37 and 2.4 times higher than the conventional till. Critical values for penetration resistance were observed for conventional till and no-till systems at 5-20 cm depth. On the other hand, in the 0-5 cm layer, the no-till presented a low value for penetration resistance, in accordance with its elevated amount of organic matter, associated with vegetal material in decomposition at soil surface. These aspects emphasize the beneficial effect of this system for the structural quality, contributing to the sustainable management of the soil.